Glass trade on the Early Islamic Silk Road: the use of electron probe microanalysis in the investigation of glass from Pella, Jordan and Qasr al-Hayr al-Sharqi, Syria - Harte, Dominic (2021)
The major and minor elemental oxide components of 49 glass samples from Pella, Jordan and 11 glass samples from Qasr al-Hayr al-Sharqi, Syria were studied using Electron Probe Microanalysis (EPMA) in order to characterise them in the context of the Early Islamic glassmaking industry. The compositional types and provenances of these glasses were determined by comparing the datasets obtained in this study to contemporary glass finds throughout the Middle East as a means of gaining insight into the production and trade of glass during this important transitional period of the Middle East. From both sites, soda-lime-silica glasses of both natron and plant ash types were discovered as well as a third miscellaneous group of unknown origin. Dated to the 9th -10th centuries CE, the findings from Pella showed that natron glass from both the Levantine coast and Egypt were being imported and potentially worked on site. Of the Qasr al-Hayr al-Sharqi glass samples dated to the 8-9th centuries CE, it was found that glass had been imported from both Egypt and the Levant as well. The plant ash glass of Qasr al-Hayr al-Sharqi was likely fused in Northern Syria, perhaps at al-Raqqa, and demonstrates one of the earliest cases of this type of glass being exported from its production zone. Plant ash glasses found at Pella were likely to have been imported from both Iraqi and Levantine primary production zones, indicating the long-distance trade occurring at the time. These findings provide a clearer image of the inter-regional trade and exchange of glass that was occurring on the Silk Road networks in the Early Islamic period as well as the greater implication of a highly diverse level of communication and interconnectedness amongst the newly united people of the Middle East.